Potential of Curcumin and Its Analogs in Glioblastoma Therapy - Agnieszka Nowacka; Ewa Ziółkowska; Wojciech Smuczyński; Dominika Bożiłow; Maciej Śniegocki (Antioxidants)
Curcumin, a polyphenol found in turmeric, demonstrates multifaceted anti-cancer activity against glioblastoma. Its therapeutic potential stems from its ability to modulate various molecular pathways implicated in glioblastoma development and progression, enhance the effectiveness of radiation therapy, and induce cancer cell death through diverse mechanisms, including apoptosis, autophagy, and cell cycle arrest. These combined actions make curcumin a promising candidate for glioblastoma treatment, warranting further investigation into its clinical application. In this review, we summarize the latest research on curcumin and its analogs’ potential in glioblastoma therapy.